2022
DOI: 10.21470/1678-9741-2020-0188
|View full text |Cite
|
Sign up to set email alerts
|

Glycated Haemoglobin Levels and Its Effect on Outcomes in Cardiac Surgery

Abstract: There remains a significant paucity of information evaluating the effect of glycated HbA1c levels and its theorized effect on mortality and morbidity rates following cardiac surgery. Diabetes is a very common comorbidity in patients undergoing open heart surgery, as there is a shift in patient characteristics and greater risk. Currently, there is no clear consensus that an increase in HbA1c level is associated with increased perioperative mortality rate. However, the reported literature is more commonly able t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 47 publications
0
9
0
1
Order By: Relevance
“…The use of drainage tubes, while essential in many surgical procedures, has been linked to an increased risk of SSIs. 15 , 16 Drainage tubes can act as a conduit for bacteria, facilitating the migration of pathogens from the skin surface to the surgical site. Additionally, their presence may cause local tissue trauma and inflammation, compromising the integrity of the wound and making it more susceptible to infection.…”
Section: Discussionmentioning
confidence: 99%
“…The use of drainage tubes, while essential in many surgical procedures, has been linked to an increased risk of SSIs. 15 , 16 Drainage tubes can act as a conduit for bacteria, facilitating the migration of pathogens from the skin surface to the surgical site. Additionally, their presence may cause local tissue trauma and inflammation, compromising the integrity of the wound and making it more susceptible to infection.…”
Section: Discussionmentioning
confidence: 99%
“…Tendo em vista de que a hemoglobina glicosilada elevada influenciou no desenvolvimento de IPFT no grupo multiarterial, levanta-se o questionamento relacionado à atual conduta das equipes médicas, onde pacientes portadores de diabetes, ou com níveis aumentados de hemoglobina glicosilada são gerenciados para o não uso da ATI bilateral e sim para métodos alternativos como enxerto de artéria radial e/ou safena, com o intuito de reduzir a probabilidade de ocorrer o desfecho de infecção. 20,21 Entretanto, nossos achados mostram que para evitar IFPT, os valores glicêmicos precisam ser estritamente corrigidos antes, durante e após a cirurgia de forma soberana à escolha dos enxertos utilizados, desta forma, acreditamos que a otimização mais criteriosa da glicemia 22,23 pode trazer mais benefícios ao paciente que simplesmente evitar o uso da ATI bilateral. Dorman et al 24 compararam retrospectivamente após PSM, pacientes diabéticos controlados e assistidos submetidos a CRM uni e multi arterial em um seguimento de 30 anos e mostraram que, por mais que o paciente fosse diabético o uso de ATI bilateral não aumentou as taxas de morbidade e tampouco de mortalidade, Zhou et al 25 também mostraram benefícios no uso da técnica mutliarterial para pacientes diabéticos devidamente controlados em sua metanálise, Estes achados reforçam a teoria colocada pelos autores deste artigo, onde o controle da glicemia do paciente é soberano à escolha dos enxertos.…”
Section: Paredes Et Al Enxertos Arteriais Na Revascularização Miocárdicaunclassified
“…2 A recent review article demonstrated that glycaemic optimisation prior to cardiac surgery improves postoperative outcomes. 3 Based on the findings of a further recent study in the United States, approximately 13% of diabetes-related total healthcare costs can be saved by a 1% (11 mmol/mol) reduction in haemoglobin A 1c (HbA 1c ). 4 The three key areas in the management of diabetes are lifestyle modification, self-management education and patient empowerment.…”
Section: The Importance Of Dietetic Input In Improving Glycaemic Cont...mentioning
confidence: 99%